2008
DOI: 10.9771/cmbio.v7i1.4361
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco da ulceração aftosa recorrente – uma revisão dos achados atuais

Abstract: A Ulceração Aftosa Recorrente (UAR) é a desordem que afeta a mucosa oral com maior freqüência, acometendo principalmente áreas não ceratinizadas. Caracteriza-se por ulcerações dolorosas, recorrentes, superficiais, circundadas por um halo eritematoso. As úlceras são classificadas de acordo com suas características clínicas em úlceras aftosas menores, úlceras aftosas maiores e úlceras herpetiformes. Sua etiologia é multifatorial, e podem estar associadas com histórico familiar, fatores locais, sistêmicos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…It has been reported that its prevalence ranges from 5% to 60% of the population. 1 , 10 In this present research, its prevalence was of 1.4% during a period of 11 years, which is lower than what is reported in the literature. This fact may suggest that many people affected by this condition do not seek odontological care for the diagnosis and treatment, since they have a short and self-limited clinical course.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations
“…It has been reported that its prevalence ranges from 5% to 60% of the population. 1 , 10 In this present research, its prevalence was of 1.4% during a period of 11 years, which is lower than what is reported in the literature. This fact may suggest that many people affected by this condition do not seek odontological care for the diagnosis and treatment, since they have a short and self-limited clinical course.…”
Section: Discussioncontrasting
confidence: 83%
“…Aphthous ulcers or recurrent aphthous stomatitis (RAS) are benign ulcerated lesions common on the mouth, with uncertain etiology, still controversial treatment and a differential diagnosis that requires attention and clinical experience. 1 , 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations